Light Scattering and Platelet Aggregation - Stoltz, J. F.; Larcan, A.; Batoz, J. F.; Streif, F. (Thrombosis and Haemostasis, 1975)
After a short recall of the theories concerning nephelometry and light scattering, the authors develop their experimental study, which is divided into three parts :- platelets absorption i.e. wave lengths- light variation curves transmitted or scattered according to platelet concentration- aggregation by nephelometric method and by light scattering.These experiments allow the authors to conclude that platelets do not present a specific absorption; that the variations of the light transmitted or scattered is exponential in function of the platelet concentration and that the aggregation test affords essentially a measurement of the decrease of the number of free platelets in the medium.Besides, they observe that the measures of aggregation kinetics, or the problem of platelet shape change are not specific and should be investigated with the help of other methods.This work was supported by D. R. M. E. grant (Biological Section).